2000
DOI: 10.1034/j.1399-3046.2000.00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric renal transplantation in Turkey:A review of 56 cases from a single center

Abstract: In order to assess certain aspects of pediatric kidney transplantation (Tx) in Turkey, we retrospectively analyzed the results of 56 of these pediatric procedures performed at our center. From January 1986 to January 1998, 56 pediatric renal Tx (29 males, 27 females; 0-17 yr of age) were carried out at Başkent University Hospital. All were first-time Tx. Fifty-one (91%) patients were on hemodialysis and four (7.3%) were on peritoneal dialysis prior to Tx. Pre-emptive Tx was performed for only one patient. Livi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 22 publications
2
6
2
Order By: Relevance
“…The results of our study where overall 1‐ and 5‐yr patient and graft survival rates were 90% and 75% and 88% and 65%, respectively, are comparable to those from the developed world, where graft survival rates are reported to be 80–90% at 1 yr and 70–80% at 5 yr (13, 15, 20). Our results were better than in some developing countries who reported a 1‐yr graft survival rate of 73–75% (34–36) and comparable to those reported from Turkey where 1‐ and 5‐yr graft survival rates were 93% and 63%, respectively (19).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The results of our study where overall 1‐ and 5‐yr patient and graft survival rates were 90% and 75% and 88% and 65%, respectively, are comparable to those from the developed world, where graft survival rates are reported to be 80–90% at 1 yr and 70–80% at 5 yr (13, 15, 20). Our results were better than in some developing countries who reported a 1‐yr graft survival rate of 73–75% (34–36) and comparable to those reported from Turkey where 1‐ and 5‐yr graft survival rates were 93% and 63%, respectively (19).…”
Section: Discussionsupporting
confidence: 77%
“…The incidence of AR episodes in the current living‐related series was higher than in our adult experience (18) as well as in some of other living‐related pediatric series with living‐related donors, which reported rejection rates of 30–57% (16, 19, 20). The high rejection rate in our series may well be a reflection of over‐reporting of rejection in the initial phases of our programme, as it was based on clinical judgements and biochemical analyses, and also our reluctance to biopsy recipients who were < 12 yr of age.…”
Section: Discussioncontrasting
confidence: 60%
“…Additionally, CAD, preemptive transplantation and retransplantation ratios were found to be lower than the ratios reported in the literature which suggested that the concept of organ donation had not improved satisfactorily yet in Turkey (7–9). Other centers in Turkey also reported similar ratios (6).…”
Section: Discussionsupporting
confidence: 64%
“…In the literature, different time intervals of dialysis prior to transplantation have been reported. Meier Kriesche et al reported the mean duration of dialysis before renal transplantation was 12–24 months, and Haberal et al reported the duration to be 7.6 months (5, 6). In our study population, the duration was 22 months.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, risk of PTKS is associated with older age at the time of transplant . Our search of the literature revealed 8 studies of a total of 25 pediatric cases of PTKS . As was seen in our patient, many prior patients who have been described presented earlier after transplant than the adult median, and pediatric patients more commonly had visceral involvement than purely cutaneous disease .…”
Section: Discussionmentioning
confidence: 74%